Combining radiotherapy and immunotherapy in definitive treatment of head and neck squamous cell carcinoma - Plavc, Gaber (Radiology and oncology (Ljubljana), 2020)
Head and neck squamous cell carcinoma (HNSCC) presents as locally advanced disease in a majority of patients and is prone to relapse despite aggressive treatment. Since immune checkpoint inhibitors (ICI) have shown clinically significant efficacy in patients with recurrent/metastatic HNSCC (R/M HNSCC), a plethora of trials are investigating their role in earlier stages of disease. At the same time, preclinical data showed the synergistic role of concurrently administered radiotherapy and ICIs (immunoradiotherapy) and explained several mechanisms behind it. Therefore, this approach is prospectively tested in a neoadjuvant, definitive, or adjuvant setting in non-R/M HNSCC patients. Due to the intricate relationship between host, immunotherapy, chemotherapy, and radiotherapy, each of these approaches has its advantages and disadvantages. In this narrative review we present the biological background of immunoradiotherapy, as well as a rationale for, and possible flaws of, each treatment approach, and provide readers with a critical summary of completed and ongoing trials. Conclusions. While immunotherapy with ICIs has already become a standard part of treatment in patients with R/M HNSCC, its efficacy in a non-R/M HNSCC setting is still the subject of extensive clinical testing. Irradiation can overcome some of the cancer%s immune evasive manoeuvres and can lead to a synergistic effect with ICIs, with possible additional benefits of concurrent platinum-based chemotherapy. However, the efficacy of this combination is not robust and details in trial design and treatment delivery seem to be of unprecedented importance.
Keywords: glava; imunoradioterapija; imunoterapija; radioterapija; rak (medicina); vrat